IMPLEMENTASI UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP TERHADAP KEBERSIHAN LINGKUNGAN MASYARAKAT - Hakim Fadhilah; Rhega Relynada; Febranisa Erin; Muhammad Rizky Fadhillah (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
In essence, environmental management which includes prevention, control of damage and pollution, as well as restoration of environmental quality requires the development of various policies and programs. Activities that are supported by other environmental management support systems, the system includes institutional stability, partnerships with human resources and the environment, in addition to legal and regulatory instruments, the availability of information and funding also need to be the main issues resolved by the Government. Law Number 32 of 2009 concerning the Protection and Management of the Environment which has the aim of ensuring the fulfillment and protection of the right to the environment as part of human rights. So to realize this goal, it is necessary to play a legal role in good and correct environmental management which is later expected to be an effort to make the public aware of the importance of making efforts to live clean and healthy behaviors. This study uses a normative juridical research method, using secondary data such as legislation, scientific journals, legal books related to community environmental management. The results obtained by the researchers in conducting this research, show that people who commit criminal acts of pollution and/or environmental destruction can be subject to criminal sanctions in accordance with what is stated in Law Number 32 of 2009 concerning Environmental Protection and Management and a strategy is needed. the right legal approach in resolving the case by optimally making use of the current regulations.